Nadużywana forma „jakby” — wtręt językowy czy też wyraz pełnowartościowy? - Быкова, Лилия (Studia Rossica Posnaniensia, 2018)
The article synthesizes, organizes and in many ways reveals and defines the conventionally invariant and derivative values (senses) of the hyperfrequency particle 'AS IF (КАК БЫ)' using as its material various discourses in the modern Russian language. Anthropological and phenomenological study revealing the pragmatic strategy of the speaker's approach to the texts, substantiated the hypothesis of the permanent dialogical, situational significance of this specific discourse phrase, even in cases when it reveals the physiological aspects of speaking. On the surface, the explanation of the reasons for the high frequency use of 'as if' is based on socio-political factors. At the same time, the ”byte of uncertainty” of our time correlates with the categories of contemporary postmodernist consciousness with its freedom from the unambiguous connection of the word with the denoter and, as a consequence, with the loss of uniqueness and certainty.